Andean Nº11 - Costa Benavides, Jimena (2025)
This eleventh issue of Andina magazine serves as a forum for critical reflection on the direction of Latin America in a global context marked by uncertainty and technological change. Under the direction of César Montaño Galarza, this issue poses the fundamental question, “Quo vadis, Latin America?”, analyzing whether the region has a strategic direction in the face of the challenges of globalization and competition between powers such as the United States and China.
Keywords: International Relations; International law; Sovereignty; historical memory; Regional cooperation